Climate change and sustainable development in Iraq (Journal of the College of Basic Education, 2026)
Climate change is a significant environmental issue, a scientific fact, and a long-term global problem involving complex interactions with economic, social, environmental, and political repercussions. The ongoing phenomenon of climate change is attributed to human activity and the misuse of available natural resources, in addition to natural causes. It is essential to strive for industrial development that meets society's basic needs, but such sustainable development must be well-thought-out and resource-intensive, ensuring its sustainability. Climate change is one of the most significant natural problems facing Iraq today. Due to its negative repercussions across various fields and human dimensions, it has become a major concern for the country and international organizations.Climate change represents a serious challenge for Iraq, as it suffers from high temperatures in the summer and a lack of rainfall in the winter, leading to a water crisis, drought, and the migration of farmers.